Upaya Meningkatkan Keterampilan Sosial dengan Menggunakan Model Social Science Inquiry Berbantuan Media Powerpoint Siswa Kelas V Sekolah Dasar - Hafizah, Nurul; Ananda, Rizki; Amalia, Rizki; Riza, Muhammad Syahrul; Sumianto, Sumianto (Universitas Negeri Makassar, 2024)
This research aims to improve the social skills of fifth-grade students at SDN 004 Salo who are learning social studies using the Social Science Inquiry learning model with the help of PowerPoint . Students' social skills are evaluated using social skills indicators. PTK is the term used to describe this type of research. 20 class V students of SDN 004 Salo were used as research subjects. Data collection techniques are carried out using observation sheets, documentation, and LTS. Data analysis techniques use quantitative descriptive and qualitative descriptive. The results of this research show that the Social Science Inquiry learning model assisted by PowerPoint media improves students' social skills. This is shown by observation data collected from 20 students in cycle I; It is known that 10 students or 50% of their social skills are included in the complete group. Based on the results from cycle I to cycle II, there were 16 students or 80% of the total category who experienced an increase in social skills. Based on this research, the Social Science Inquiry learning model assisted by PowerPoint media can improve the social skills of class V students at SDN 004 Salo.